2007
DOI: 10.1103/physreve.76.011926
|View full text |Cite
|
Sign up to set email alerts
|

Model for Osteosarcoma-9 as a potent factor in cell survival and resistance to apoptosis

Abstract: In this paper we use a simple model to explore the function of the gene Osteosarcoma-9. We are in particular interested in understanding the role of this gene as a potent anti-apoptotic factor.The theoretical description is constrained by experimental data from induction of apoptosis in cells where OS-9 is overexpressed. The data available suggest that OS-9 promotes cell viability and confers resistance to apoptosis, potentially implicating OS-9 in the survival of cancer cells. Three different apoptosis-induci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Functionally, it has been implicated in ER-to-Golgi transport of the membrane protease and helps to select misfolded glycoproteins for degradation 18 , 19 . Recently, Carvalho and colleagues showed that OS-9 is involved in cell survival and resistance to apoptosis 20 . Should be note, the current studies suggested that OS-9 may affects hypoxic signaling via interaction with either the transcription factor HIF-1α or an HIF-1α-independent pathway 14 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, it has been implicated in ER-to-Golgi transport of the membrane protease and helps to select misfolded glycoproteins for degradation 18 , 19 . Recently, Carvalho and colleagues showed that OS-9 is involved in cell survival and resistance to apoptosis 20 . Should be note, the current studies suggested that OS-9 may affects hypoxic signaling via interaction with either the transcription factor HIF-1α or an HIF-1α-independent pathway 14 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…OS‐9 overexpression reduced the protein levels of HIF‐1 α , and the degradation of OS‐9 mRNA leads to increased HIF‐mediated transcription under both normoxic and hypoxic conditions. OS‐9 is able to form a complex with HIF‐1 α and PHD2 or PHD3, promoting the hydroxylation of HIF‐1 α and subsequent proteasomal degradation 57,58 . The observed expression of OS‐9 in human tumours expressing elevated HIF levels points towards a potential dominant‐negative form of OS‐9 in tumours 18,57 .…”
Section: Regulation Of Hifmentioning
confidence: 99%
“…p53 has a key role in mediating cellular response to various stress signals, mainly by inducing or repressing a number of proteins that are involved in cancer cell cycle progression and apoptosis (14). Clinically, apoptotic resistance has become one of the greatest challenges in cancer therapy due to fierce resistance of tumor cells through various molecular mechanisms (15,16). Thus, underlying molecular mechanism of apoptotic resistance and exploring more efficacy target therapies are urgently required to improve the overall survival rate for patients with osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%